Gegen Barbarei : Essays Robert M. W. Kempner zu Ehren - Eisfeld, Rainer 1941- Hrsg; Kempner, Robert M. W. 1899-1993 GefeierteR (Athenäum-Verl, 1989)
Rainer Eisfeld und Ingo Müller (Hrsg.): Gegen Barbarei. Essays Robert M. W. Kempner zu Ehren. Athenäum/Hain, Frankfurt a. M. 1989. 515 Seiten, 48,- DM